Bridging Digital Communication Amongst Digital Natives - Yakobus Suharyono (MUKASI: Jurnal Ilmu Komunikasi, 2022)
Distance learning becomes critical alternative in educational practices. Digital technology is becoming an opportunity. Don Tapscott’s net-gen proposes the upcoming phenomenon of the digital-natives which are somewhat different from those of digital-immigrants. This research observed digitally distance educational learning teaching activity occured amongst digital-natives conduted by using GoogleMeet, GoogleClassroom, WhatsApp platform and YouTube.com Channel. It aims to portray how distance learning activity was implemented amongst the elementary students in the era of covid-19 pandemic in Bekasi. The observation was done by joining into social media group of students and teachers. The result shows that both interpersonal perspectives and educational philosophical aspects must be put together sinergically into distance class on the basis of technological competences and literacy in educational environment on which the value of social compassions amongst learners must be encouraged too. When they are sinergically melted in the process of learning communication and relations, the optimal academic performance was possibly gained.